2019
DOI: 10.1200/jop.18.00705
|View full text |Cite
|
Sign up to set email alerts
|

Olaparib-Induced Severe Folate Deficiency in a Patient With Advanced Ovarian Cancer

Abstract: Author affiliations and support information (if applicable) appear at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 1 publication
(2 reference statements)
2
9
0
Order By: Relevance
“…19 Several studies had also shown that the incidences of anemia, thrombocytopenia, neutropenia were about 50%, 30% and 25%, respectively. 3,20,21 In addition, significant AEs signal strengths of myelodysplastic syndrome (MDS) and acute myeloid leukaemia (AML) were presented in our analysis, which were corresponding to that in the instruction and clinical safety data. 22 Folate deficiency was reported as a new and significant AE of olaparib with signal strength being ROR 18.99 (8.48-42.54), ), IC 4.23 (1.00) and EBGM 18.72 (8.36), respectively, in our results.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…19 Several studies had also shown that the incidences of anemia, thrombocytopenia, neutropenia were about 50%, 30% and 25%, respectively. 3,20,21 In addition, significant AEs signal strengths of myelodysplastic syndrome (MDS) and acute myeloid leukaemia (AML) were presented in our analysis, which were corresponding to that in the instruction and clinical safety data. 22 Folate deficiency was reported as a new and significant AE of olaparib with signal strength being ROR 18.99 (8.48-42.54), ), IC 4.23 (1.00) and EBGM 18.72 (8.36), respectively, in our results.…”
Section: Discussionsupporting
confidence: 65%
“… 19 Several studies had also shown that the incidences of anemia, thrombocytopenia, neutropenia were about 50%, 30% and 25%, respectively. 3 , 20 , 21 In addition, significant AEs signal strengths of myelodysplastic syndrome (MDS) and acute myeloid leukaemia (AML) were presented in our analysis, which were corresponding to that in the instruction and clinical safety data. 22 …”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…anemia, as severe folate deficiency contributing to anemia was observed in a small number of patients receiving olaparib in the relapsed disease setting; administering folate supplements ameliorated the requirement for transfusion and olaparib dose modification in one patient [14].…”
Section: Discussionmentioning
confidence: 99%
“…Not only may patients and their close relatives become aware of being at increased risk of developing various cancer types, pathogenic BRCA1/2 variants are also treatment targets for poly ADP-ribose polymerase (PARP) inhibitors (33). Clinical complications related to anti-cancer treatment regimens (34)(35)(36) furthermore led to the development of genomic assays such as the 70-gene MammaPrint microarray with level 1A evidence of clinical utility for prediction of chemotherapy benefit (37). Microarray analysis using tumor samples reformed our past understanding of BC as a single disease to a complex disorder consisting of at least four major subtypes, namely luminal A, luminal B, HER2-enriched and basal-type.…”
Section: Discussionmentioning
confidence: 99%